1991
DOI: 10.1093/nar/19.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the genomic distribution of alpha satellite DNA on all the human chromosomes, and derivation of a new consensus sequence

Abstract: A survey of the genomic distribution of alpha satellite DNA on all the human chromosomes, and derivation of a new consensus sequence by K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
3
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(133 citation statements)
references
References 29 publications
2
126
3
1
Order By: Relevance
“…Alphoid DNA flanking an L1 could be transduced to a new location during the L1 retrotransposition event, and would produce small stretches of alphoid DNA sites outside of their normal centromeric locations. However, the synthesized 18-mer PNA probe, designed on the basis of the consensus sequence of alphoid DNA (Choo et al 1991), did not show any such hybridization signals outside the centromeric regions of chromosomes under the present experimental conditions. The relative fluorescence intensities of centromeric signals were as follows: chromosomes 9, 14, 18, 20, and 22 exhibited strong signals; chromosomes 1, 3, 8, 12 and 16 showed weak signals; other chromosomes (chromosomes 2, 4, 5, 6, 7, 10, 11, 13, 15, 17, 19, 21 and X) exhibited signals with intermediate intensity.…”
Section: Distribution Of the Hybridization Signals Of Pna Probe For Tcontrasting
confidence: 63%
“…Alphoid DNA flanking an L1 could be transduced to a new location during the L1 retrotransposition event, and would produce small stretches of alphoid DNA sites outside of their normal centromeric locations. However, the synthesized 18-mer PNA probe, designed on the basis of the consensus sequence of alphoid DNA (Choo et al 1991), did not show any such hybridization signals outside the centromeric regions of chromosomes under the present experimental conditions. The relative fluorescence intensities of centromeric signals were as follows: chromosomes 9, 14, 18, 20, and 22 exhibited strong signals; chromosomes 1, 3, 8, 12 and 16 showed weak signals; other chromosomes (chromosomes 2, 4, 5, 6, 7, 10, 11, 13, 15, 17, 19, 21 and X) exhibited signals with intermediate intensity.…”
Section: Distribution Of the Hybridization Signals Of Pna Probe For Tcontrasting
confidence: 63%
“…(A) Schematic drawings of the alphoid tetO DNA array and tetR fusion constructs expressed in HeLa 1C7 cells. The synthetic monomer was based on a published consensus sequence for alphoid DNA (Choo et al, 1991). (B) Real-time RT-PCR analysis of non-transfected 1C7 cells stably carrying the alphoid tetO HAC and 2 days after transfecting constructs expressing tetR-EYFP (tetR), tetR-EYFP-p65 (p65) or tetR-EYFP-VP16 (VP16).…”
Section: Resultsmentioning
confidence: 99%
“…In humans, endogenous centromeres typically form on chromosome-specific higher-order 'alphoid' DNA arrays, which are composed of 171 bp alpha-satellite monomer units that are tandemly arranged in a directional head-to-tail fashion (Choo et al, 1991;Mitchell et al, 1985;Schueler and Sullivan, 2006;Willard and Waye, 1987). Independent of this sequence preference, specific deposition of the centromeric histone H3 variant CENP-A (Earnshaw and Rothfield, 1985) is thought to form the basis for an 'epigenetic' maintenance of centromere identity (Allshire and Karpen, 2008;Okamoto et al, 2007;Vafa and Sullivan, 1997;Warburton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Even the so-called DNA alpha satellite sequences are heterogeneous and each centromere differs in DNA subtypes. [33][34][35][36][37][38][39] Moreover functional centromeres can lack alphoid DNA. [40][41][42][43] It has been shown that the heterochromatin of some chromosomes such as chromosome 1 could be uncoiled by the hypomethylating agent azacytidine.…”
Section: Discussionmentioning
confidence: 99%